Climatic clustering analysis for novel atlas mapping and bioclimatic design recommendations. Issue 3 (March 2021) - Roshan, Gholamreza; Farrokhzad, Mohammad; Attia, Shady
Defining and determining climatic zones accurately is crucial to inform the decision making of building designers and planners during early design phases of urban development. Characterizing the climatic zones allows estimation of energy requirements in buildings and develop climate adapted energy polices. Climatic zones can be defined by using the statistical cluster analysis. Data from weather stations can be used after standardization with zero mean and unit variance, to confirm that all variables are weighted equally in the cluster analysis. In this paper, a novel atlas for 19 climatic zones is presented that represent a variety of bioclimatic design strategies and recommendations, for passive design, based on a clustering analysis in Iran. The clustering analysis is based on the statistical analysis of daily temperature and relative humidity from 1995 to 2014. The results visualize 19 different climate zones for Iran and indicate the dominance of passive design strategies. As a result, Iran was divided into eight climatic clusters. The results showed that each of the studied clusters require specific strategies in providing indoor comfort. The outputs of this study shed the light on the importance of up-to-date climate characterization and the effectiveness of climate mapping and recommendations to inform decision makers.